A Gallium‐Substituted Distibene and an Antimony‐Analogue Bicyclo[1.1.0]butane: Synthesis and Solid‐State Structures. Issue 36 (6th August 2015) - Tuscher, Lars; Ganesamoorthy, Chelladurai; Bläser, Dieter; Wölper, Christoph; Schulz, Stephan
Abstract RGa R=HC[C(Me)N(2, 6‐iPr2C6H3)]2 reacts with Sb(NMe2)3 with insertion into the SbN bond and elimination of RGa(NMe2)2 (2), yielding the Ga‐substituted distibene R(Me2N)GaSbSbGa(NMe2)R (1). Thermolysis of 1 proceeded with elimination of RGa and 2 and subsequent formation of the bicyclo[1.1.0]butane analogue [R(Me2N)Ga]2Sb4 (3).